Cadmium telluride (CdTe) and cadmium selenide (CdSe) leaching behavior and surface chemistry in response to pH and O2. (1st May 2015) - Zeng, Chao; Ramos-Ruiz, Adriana; Field, Jim A.; Sierra-Alvarez, Reyes
Abstract: Cadmium telluride (CdTe) and cadmium selenide (CdSe) are increasingly being applied in photovoltaic solar cells and electronic components. A major concern is the public health and ecological risks associated with the potential release of toxic cadmium, tellurium, and/or selenium species. In this study, different tests were applied to investigate the leaching behavior of CdTe and CdSe in solutions simulating landfill leachate. CdTe showed a comparatively high leaching potential. In the Toxicity Characteristic Leaching Procedure (TCLP) and Waste Extraction Test (WET), the concentrations of cadmium released from CdTe were about 1500 and 260 times higher than the regulatory limit (1 mg/L). In contrast, CdSe was relatively stable and dissolved selenium in both leaching tests was below the regulatory limit (1 mg/L). Nonetheless, the regulatory limit for cadmium was exceeded by 5- to 6- fold in both tests. Experiments performed under different pH and redox conditions confirmed a marked enhancement in CdTe and CdSe dissolution both at acidic pH and under aerobic conditions. These findings are in agreement with thermodynamic predictions. Taken as a whole, the results indicate that recycling of decommissioned CdTe-containing devices is desirable to prevent the potential environmental release of toxic cadmium and tellurium in municipal landfills. Highlights: CdTe showed a high leaching potential. The limit for Cd was exceeded 260- to 1500-fold in WET and TCLP tests with CdTe. CdSe was relatively stable in aqueous solution. Dissolution of CdTe and CdSe is favored by oxidizing and acidic conditions. Proper end-of-life management is required for CdTe-containing devices.